Why we believe what we believe - "Newberg , Andrew" (New York, 2006)
WHY DO YOU BELIEVE THE THINGS YOU BELIEVE? Do you remember events differently from how they really happened? Where do your superstitions come from? How do morals evolve? Why are some people religious and others nonreligious? Everyone has thoughts and questions like these, and now Andrew Newberg and Mark Waldman expose, for the first time, how our complex views emerge from the neural activities of the brain. Bridging science, psychology, and religion, they demonstrate, in simple terminology, how the brain perceives reality and transforms it into an extraordinary range of personal, ethical, and creative premises that we use to build meaning, value, spirituality, and truth into our lives. When you come to understand this remarkable process, it will change forever the way you look at the world and yourself. Supported by groundbreaking research, including brain scans of people as they pray, meditate, and even speak in tongues, Newberg and Waldman propose a new model for how deep convictions emerge and influence our lives. You will even glimpse how the mind of an atheist works when contemplating God. Using personal stories, moral paradoxes, and optical illusions, the authors demonstrate how our brains construct our fondest assumptions about reality, offering recommendations for exercising your most important "muscle" in order to develop a more life-affirming, flexible range of attitudes. You'll discover how to: Recognize when your beliefs are altered by others Guard against mental traps and prejudicial thinking Distinguish between destructive and constructive beliefs Cultivate spiritual and ethical ideals Ultimately, we must always return to our beliefs. From the ordinary to the extraordinary, they give meaning to the mysteries of life, providing us with our individual uniqueness and the ability to fill our lives with joy. Most important, though, they give us inspiration and hope, beacons to guide us through the light and dark corners of the soul.
Keywords: "Psychology , religious"